(untitled) (Scientific journal of the Fergana State University, 2025)
The article studies the theoretical foundations of the socio-philosophical analysis of the place of fine and applied arts in building an enlightened society in New Uzbekistan, the socio-cognitive potential of fine and applied arts in building an enlightened society in New Uzbekistan, the future tasks of developing fine and applied arts in building an enlightened society in New Uzbekistan. Also, the issues of developing fine and applied arts in building an enlightened society in New Uzbekistan are analyzed.